Why does stress aggravate itch? A possible role of the amygdala. Issue 12 (15th May 2019) - Pavlenko, Darya; Akiyama, Tasuku
Abstract: Stress is the exacerbating factor of itch across patients with chronic itch due to different origins. However, the precise mechanisms behind stress‐induced exacerbation of itch remain unknown. Chronic stress induces hyperexcitability of the amygdala, the centre of emotional processing. Recent findings on the itch neuronal pathways support a pivotal role of the amygdala for itch processing. We hypothesized that itch is enhanced by stress through hyperexcitation of the amygdala. Modulation of amygdala activity, therefore, may have therapeutic potential in the treatment of chronic itch.